Think like a monk : train your mind for peace and purpose every day - Shetty, Jay (New York : Simon & Schuster Paperbacks, 2020)
"Jay Shetty draws on his experience as a monk to share practical steps for reducing stress, finding purpose, and developing lasting peace of mind through mindfulness and self-discipline."
Includes bibliographical references.
Keywords: Self-management (Psychology).; Mindfulness (Psychology); Success -- Psychological aspects